Exposure to indoor mould and children's respiratory health in the PATY study. Issue 8 (11th July 2008) - Antova, T; Pattenden, S; Brunekreef, B; Heinrich, J; Rudnai, P; Forastiere, F; Luttmann-Gibson, H; Grize, L; Katsnelson, B; Moshammer, H; Nikiforov, B; Slachtova, H; et al.
Abstract : Background: Living in a damp or mouldy home reportedly damages children's respiratory health, yet mould appears not to be a prominent risk factor in the public's perception. Analyses of data on over 58 000 children from the Pollution and the Young (PATY) study are presented. In this collaboration, researchers from 12 cross-sectional studies pooled their data to assess the effects of air quality on a spectrum of children's respiratory disorders. Method: Original studies were conducted in Russia, North America and 10 countries in Eastern and Western Europe. Pooled analyses were restricted to children aged 6–12 years. Associations between visible mould reported in the household and a spectrum of eight respiratory and allergic symptoms were estimated within each study. Logistic regressions were used, controlling for individual risk factors and for study area. Heterogeneity between study-specific results and mean effects (allowing for heterogeneity) were estimated using meta-analysis. Results: Visible mould was reported by 13.9% of respondents in Russia, increasing to 39.1% in North America. Positive associations between exposure to mould and children's respiratory health were seen with considerable consistency across studies and across outcomes. Confounder-adjusted combined ORs ranged from 1.30 (95% CI 1.22 to 1.39) for "nocturnal cough" to 1.50 (1.31 to 1.73) for "morning cough". Evidence of stronger effects in more crowded households was statistically significant for only asthma and sensitivity to inhaled allergens. No consistent interactions between mould and age, sex or parental smoking were found. Conclusion: Indoor mould exposure was consistently associated with adverse respiratory health outcomes in children living in these diverse countries.